An oncolytic adenovirus delivering TSLC1 inhibits Wnt signaling pathway and tumor growth in SMMC-7721 xenograft mice model. (30th April 2021) - Wang, Yigang; Huang, Panpan; Hu, Yanping; Guo, Keni; Jia, Xiaoyuan; Huang, Biao; Liu, Xinyuan; He, Xianglei; Huang, Fang
Abstract: Tumor suppressor in lung cancer-1 (TSLC1) was first identified as a tumor suppressor for lung cancer, and frequently downregulated in various types of cancers including hepatocellular carcinoma (HCC). The Wnt pathway plays a critical role in tumorigenesis, migration, and invasion in HCC. However, the function of TSLC1 in modulating Wnt signaling in HCC is unclear. In this study, we evaluated the effect of TSLC1-armed oncolytic adenovirus (S24-TSLC1) on the Wnt/β-catenin pathway, cell viability, invasion and migration abilities of HCC in vitro and the growth of SMMC-7721-xenografted tumor in mice model. We detected the expression of TSLC1 in tumor samples and HCC cell lines. The results showed that TSLC1 expression was low in HCC, but high in pericarcinomatous tissue and normal cells, which implied that TSLC1 is a tumor suppressor of liver cancer. S24-TSLC1 exhibited an antitumor effect on HCC cell growth in vitro, but did little damage to normal liver cells. Overexpression of TSLC1 downregulated the transcriptional activity of TCF4/β-catenin and inhibited the mRNA or protein expression of Wnt target genes cyclinD1 and c-myc . S24-TSLC1 also inhibited the invasion and migration of HCC cells. Animal experiments further confirmed that S24-TSLC1 significantly inhibited tumor growth of the SMMC-7721-xenografted tumor. In conclusion, TSLC1 could downregulate the Wnt signal pathway and suppress HCC cell growth, migration and invasion, suggesting that S24-TSLC1 may be a potent antitumor agent for future clinical trials in liver cancer treatment.